2014
DOI: 10.1093/nar/gkt1370
|View full text |Cite
|
Sign up to set email alerts
|

Cellular localization and dynamics of the Mrr type IV restriction endonuclease of Escherichia coli

Abstract: In this study, we examined the intracellular whereabouts of Mrr, a cryptic type IV restriction endonuclease of Escherichia coli K12, in response to different conditions. In absence of stimuli triggering its activity, Mrr was found to be strongly associated with the nucleoid as a number of discrete foci, suggesting the presence of Mrr hotspots on the chromosome. Previously established elicitors of Mrr activity, such as exposure to high (hydrostatic) pressure (HP) or expression of the HhaII methyltransferase, bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 46 publications
3
17
0
Order By: Relevance
“…Briefly, the MG1655 chromosomal mrr locus was first replaced by a tetA-sacB cassette (yielding MG1655 Δmrr::tetA-sacB ) obtained from a polymerase chain reaction (PCR) amplicon (using primers 5΄-TAGTGCTATAGTAGCCGAAAAACATCTACCTGATTCTGCAAG GATGTACTTCCTAATTTTTGTTGACACTCTATC-3΄ and 5΄-AAGGGGTTATGGGCCGGATAAGGCGC AGCCGCATCCGGCCTGATATTTCAATCAAAGGGAAAACTGTCCATATGC-3΄ on genomic DNA of E. coli T-Sack ( 17 )), after which this tetA-SacB cassette was replaced by the gfp-mrr construct of interest using Tet/SacB counter-selection media ( 17 ). For construction of the E. coli MG1655 P mrr -gfp::mrr strain, chromosomally expressing the GFP-Mrr fusion protein from the native mrr promoter, the chromosomal Δmrr::tetA-sacB allele was replaced with the gfp::mrr allele obtained from a PCR amplicon prepared on the pBAD- gfp::mrr vector (( 9 ); using primers 5΄-ATTTTTGTAGTGCTATAGTAG CCGAAAAACATCTACCTGATTCTGCAAGGATGTACTATGAGTAAAGGAGAAGAAC-3΄ and 5΄-CGAT AAGCTTG CGTTTGCGGGGTTGAGG -3΄). For construction of the E. coli K12 MG1655 P BAD -gfp::mrr strain, chromosomally expressing the GFP-Mrr fusion protein from an arabinose inducible promoter, the chromosomal Δmrr::tetA-sacB allele was replaced with the P BAD -gfp::mrr allele obtained from a PCR amplicon prepared on the pBAD- gfp::mrr vector ( 9 ) (using primers 5΄-ATTTTTGTAGTGCTAT AGTAGCCGAAAAACATCTACCTGATTCTGCAAGGATGTACTTTATGAC AACTTGACGGCTA-3΄ and 5΄-CGATAAGCTTGCGTTTGCGGGGTTGAGG-3΄).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Briefly, the MG1655 chromosomal mrr locus was first replaced by a tetA-sacB cassette (yielding MG1655 Δmrr::tetA-sacB ) obtained from a polymerase chain reaction (PCR) amplicon (using primers 5΄-TAGTGCTATAGTAGCCGAAAAACATCTACCTGATTCTGCAAG GATGTACTTCCTAATTTTTGTTGACACTCTATC-3΄ and 5΄-AAGGGGTTATGGGCCGGATAAGGCGC AGCCGCATCCGGCCTGATATTTCAATCAAAGGGAAAACTGTCCATATGC-3΄ on genomic DNA of E. coli T-Sack ( 17 )), after which this tetA-SacB cassette was replaced by the gfp-mrr construct of interest using Tet/SacB counter-selection media ( 17 ). For construction of the E. coli MG1655 P mrr -gfp::mrr strain, chromosomally expressing the GFP-Mrr fusion protein from the native mrr promoter, the chromosomal Δmrr::tetA-sacB allele was replaced with the gfp::mrr allele obtained from a PCR amplicon prepared on the pBAD- gfp::mrr vector (( 9 ); using primers 5΄-ATTTTTGTAGTGCTATAGTAG CCGAAAAACATCTACCTGATTCTGCAAGGATGTACTATGAGTAAAGGAGAAGAAC-3΄ and 5΄-CGAT AAGCTTG CGTTTGCGGGGTTGAGG -3΄). For construction of the E. coli K12 MG1655 P BAD -gfp::mrr strain, chromosomally expressing the GFP-Mrr fusion protein from an arabinose inducible promoter, the chromosomal Δmrr::tetA-sacB allele was replaced with the P BAD -gfp::mrr allele obtained from a PCR amplicon prepared on the pBAD- gfp::mrr vector ( 9 ) (using primers 5΄-ATTTTTGTAGTGCTAT AGTAGCCGAAAAACATCTACCTGATTCTGCAAGGATGTACTTTATGAC AACTTGACGGCTA-3΄ and 5΄-CGATAAGCTTGCGTTTGCGGGGTTGAGG-3΄).…”
Section: Methodsmentioning
confidence: 99%
“…While Mrr can harmlessly be expressed in cells under atmospheric conditions, fluorescence microscopy has shown that its activation by HP causes nucleoid condensation and concomitant confinement of nucleoid associated Mrr proteins (9). HP activation of Mrr triggers a RecA-dependent SOS response, underscoring that active Mrr causes double strand breaks in the host nucleoid (8).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…al., 2001). Whilst, StyLT2Mrr was primarily recognized as an enzyme conferring genotoxicity on heterologous expression of some exotic type II MTases in E. coli K12 (Ghosh et. al., 2014).…”
Section: Restriction-modification Systems (Rms)mentioning
confidence: 99%
“…The response of E. coli to pressure was stronger than for the other two microbes ( The MG1655 reference strain of E. coli used in these experiments harbored a pressureactivated restriction endonuclease, Mrr, which leads to a pressure-induced SOS response (15,23,24). To ascertain whether response of E. coli metabolism to pressure was linked to this Mrrinduced SOS response, we carried out FLIM/Phasor analysis on the auto-fluorescence of an E.…”
Section: Microbial Metabolic Responses To Pressurementioning
confidence: 99%